CHARACTER BUILDING THROUGH TRANSLATION: MISSION IMPOSSIBLE? - Havid Ardi (International Conference on Languages and Arts, 2014)
This paper aims at discussing, values and characters in translation process that must be taught to the students in order to produce good translation. In the translation process, translators face various problems whether untranslatability issues, culture, and ideology. To resolve these problems translators are required to have the competence and intelligence of selecting the best strategy. To that end, in teaching translation skill, the students are trained to not easily give up, choosing a good diction, and the best way to convey the message contained in the target language. Translators are required to be honest but should not be too honest/plain. Translators must not add or subtract in the target language, but the translator may add and reduce information. This principles seem ambiguous, could it be done is teaching process?   Keywords: translation, characters building, translation competencies.